Effect of Hospital Volume on Outcomes of Transcatheter Mitral Valve Repair: An Early US Experience. (October 2015) - Patel, Nileshkumar J.; Badheka, Apurva O.; Jhamnani, Sunny; Panaich, Sidakpal S.; Singh, Vikas; Patel, Nilay; Arora, Shilpkumar; Grines, Cindy L.; Cleman, Micheal; Forrest, John K.
<x xml:space="preserve">Abstract</x> Background Transcatheter mitral valve repair (TMVR) is a complex procedure for patients with mitral regurgitation who cannot get surgery. However, there is a lack of data on how hospital volumes affect these outcomes. Methods We performed a cross sectional study based on Healthcare Cost and Utilization Project's Nationwide Inpatient Sample database of 2012 and identified subjects using the ICD‐9‐CM procedure code of 35.97, which was introduced in October 2010 for percutaneous mitral valve repair if present in the primary or secondary procedure field. Hospital volumes were divided into tertiles. The primary outcome was a composite of in‐hospital mortality and peri‐procedural complications. Length of stay and hospitalization cost were also assessed. Results A total of 95 (weighted n = 475) TMVR procedures were identified. The mean age of the overall cohort was 70 years; 43.2% were female and 63.2% had a significant baseline burden of co‐morbidities. The composite of in‐hospital mortality and peri‐procedural complications decreased with increasing TMVR hospital volume: 48.7% in the first tertile, 17.4% in the second tertile, and 9.1% in the third tertile. Additionally, we saw a decrease in the length of stay and a trend in decrease in the hospitalization cost. Conclusion In hospitals performing TMVR, higher hospital volumes are associated with a reduction in a composite of in‐hospital mortality and post‐procedural complications, in addition to the shorter length of stay. (J Interven Cardiol 2015;28:464–471)